If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 4 = 8y + -2 Reorder the terms: 4 + 6y = 8y + -2 Reorder the terms: 4 + 6y = -2 + 8y Solving 4 + 6y = -2 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 4 + 6y + -8y = -2 + 8y + -8y Combine like terms: 6y + -8y = -2y 4 + -2y = -2 + 8y + -8y Combine like terms: 8y + -8y = 0 4 + -2y = -2 + 0 4 + -2y = -2 Add '-4' to each side of the equation. 4 + -4 + -2y = -2 + -4 Combine like terms: 4 + -4 = 0 0 + -2y = -2 + -4 -2y = -2 + -4 Combine like terms: -2 + -4 = -6 -2y = -6 Divide each side by '-2'. y = 3 Simplifying y = 3
| (5.25x-5.67)-2.6x=(6.38-5.06x) | | 7/2a=17 | | 24g^2+88g-48=0 | | 4/7*5/7*6/7 | | 2c-17-18=17 | | 15=(0.52)(6.6)+(0.52+x)(5) | | x+-3y=4v | | u/4-2.1=14.9 | | 6y^2=27y | | 44-6x=20 | | -2(-3x+1)=-4x+5 | | f(45)=0.81+168.3 | | -6(x-4)=-8(x-6) | | f(x)=3x^2-11x | | 1/2x^5=64 | | -6(-8x-4)=-7 | | 3(x+2)+x=2(3+2x) | | 3e^2x-1=0 | | X^2-100=(x+c)(x+d) | | -1/4v-4/3=7/4v-1 | | 4(x-2)-1=-4(-6x+3)-5x | | 4X+4Y-16=0 | | -6x-24=4x+3 | | 2-3(x+1)=1-2(1+0.5x) | | 4x^2-121x+225=0 | | -3(u+5)=3u-5+2(2u+4) | | -5(-5x+3)=-8x+3 | | -3(13+4x)=-4(-14+2x)+9 | | (2*x-2)/6=3 | | 2x-2/6=3 | | -n-n=12(10-13n)-12(n+10) | | (6b+48)-(27b-36)= |